Principal Leadership, Organizational Culture, and Work Motivation: Determinants of Teachers' Pedagogic Competency at Inclusion Schools in Sleman Regency - Lidya Puspita Sari; Maya Novita Sari (Journal of Educational Sciences, 2026)
Inclusive education requires teachers to have adaptive pedagogic competencies, based on the results of in-depth observations and interviews, many teachers in high school/equivalent in Sleman Regency still face obstacles in developing pedagogic competence, especially in adapting learning strategies to the diversity of students and compiling responsive teaching materials. This study aims to measure and analyze both partially and simultaneously the influence of principals' leadership, organizational culture, and work motivation on teachers' pedagogic competence in inclusion schools at the high school/equivalent level in Sleman Regency. The research uses a quantitative approach with a survey method. The results of the study show that: (1) the leadership of the principal has a positive and significant effect on the pedagogic competence of teachers (Sig. 0,003 < 0,05), (2) organizational culture has a positive and significant effect (Sig. 0.001 < 0.05), (3) teachers' work motivation has a positive and significant effect (Sig. 0.000 < 0.05), and (4) principal's leadership, organizational culture, and teachers' work motivation simultaneously have a positive and significant effect on teachers' pedagogic competence (Sig. 0.000 < 0.05). The value of the determination coefficient (R²) was 0.575, which means that independent variables were able to explain 57.5% of the variation in teachers' pedagogic competence.